Biuletyn Informacyjny "Obozu" . no. 37, 1988 - Ananicz, Andrzej ("Obóz", 1988)
Creation and circulation: In 1984-1988 publication for internal use of editors of independent periodicals. From issue no. 40(3.11.1988) published for the wider audience.